Circumstances and causes of fatal cycling crashes in the Czech Republic - Bil, Michal; Bilova, Martina; Dobias, Martin; Andrasik, Richard (Traffic injury prevention, 2016)
Objectives: The circumstances and causes of death of 129 cyclists registered in the Olomouc and the Zlín regions, the Czech Republic, between 2005 and 2013 were the subject of this study. Methods: We analyzed the autopsy reports, where the principal cause of death was stated, and obtained a detailed description of the circumstances recorded by the police officers. Results: Eighty-three cases (64.3% of the set) were collisions involving a motor vehicle. The driver was the guilty party in 57 cases (68.7%) and the cyclist in the remaining 26 cases (31.3%). The most frequent cause of the crash was connected with right of way (29 cases). Cars were involved in 52 cases; heavy vehicles, including buses, in 26 cases; and motorcycles in 5 cases. Single-vehicle crashes consisted of 43 (33.3%) cases. We divided this group into 3 subgroups based on whether the particular case could be attributed to a cyclist having lost control of the bicycle (31 cases) or to other particular causes. Sixty-eight cases (52.7%) of fatal outcomes were directly linked to intracranial injuries. Multiple injuries were the principal cause of death in 19 cases (14.7%), followed by hemorrhagic traumatic shock (12 cases, 9.3%). Seventy-two (55.8%) cyclists died immediately after the crash and 23 (17.8%) cyclists died within a day of the accident. Conclusions: Trucks were more dangerous to cyclists than cars at intersections, whereas cars were more dangerous on straight sections. The most important pattern was identified as a motor vehicle hitting a cyclist from behind on a straight road section. We identified a strong underestimation of natural death as a cause of cycling fatalities in the official police reports.